Theatrocracy : Greek Drama, Cognition, and the Imperative for Theatre - Meineck, Peter (Taylor and Francis, 2017)
Cover -- Title -- Copyright -- Dedication -- Contents -- Acknowledgements -- Introduction: theatre as a mimetic mind -- Distributed cognition -- Prediction -- Emotions -- Comparative social modeling -- Empathy -- The mimetic mind -- 1 Muthos: probability and prediction -- Making sense of surprisal -- Basic Bayes -- Probabilistic politics -- Extending prediction -- 2 Opsis: the embodied view -- Environment and action -- Phantasia theatre -- The seeing place of Dionysos -- Re-thinking open-air theatre -- The four realms of theatrical three-dimensional space -- Dionysos and dopamine -- 3 Ethos: the character of catharsis -- Mask as theatrical frame -- The affective mask -- Projecting emotions -- The mutable mask -- Peripheral and foveal vision -- Kuleshovian contexts -- The mask in its cultural and cognitive context -- Culture, literacy, and face processing -- A cognitive change of masks -- 4 Dianoia: intention in action -- Perception and action -- The action-orientated spectator -- Kinesthetic emotional contagion -- Mitigating mirror neurons -- Whole body perception -- Sensorimotor gestures -- Chorality and empathy -- 5 Melos: music and the mind -- Cross-cultural music -- The super-expressive aulos -- The dissonant lament -- A musical tragic paradox -- Musical dissonance and absorption -- Prediction and musical expectancy -- 6 Lexis: somatosensory words -- The movement of meter -- Masked language -- Linguistic evaluative conditioning -- A somatosensory analysis of Aeschylus -- Understanding the unintelligible -- 7 Metabasis: dissociation and democracy -- The Default Mode Network -- En xena xenon - "a stranger in a strange land" -- Dissociation - absorption - empathy -- Ancient empathy in action -- Coda: ancient empathy today -- Index.